Welcome to Camp Nightmare - Stine, R. L. (New York : Scholastic, 1993)
A creepy thriller about a nine-year-old boy whose summer stay at Camp Nightmoon becomes a living nightmare.
"The Goosebumps book series created by Parachute Press, Inc."--T.p. verso.
Includes preview of "The ghost next door."
Accelerated Reader AR
Keywords: Camps -- Juvenile fiction; Boys -- Juvenile fiction; Horror fiction